2014
DOI: 10.1002/dev.21241
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal handling: An overview of the positive and negative effects

Abstract: As one of the first rodent models designed to investigate the effects of early-life experiences, the neonatal handling paradigm has helped us better understand how subtle changes in the infant environment can powerfully drive neurodevelopment of the immature brain in typical or atypical trajectories. Here, we review data from more than 50 years demonstrating the compelling effects of neonatal handling on behavior, physiology, and neural function across the lifespan. Moreover, we present data that challenge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 145 publications
7
73
0
5
Order By: Relevance
“…Therefore, the harmful effects of deprivation, such as impaired development, especially sensorineural, weight gain, length of hospital stay and irritability, among others, should be considered. (31)(32) The preterm infants remained, on average, more time in QS, followed by AS and IS, contrary to a study that reported the predominance of AS, during approximately 80% of the total time, mainly in preterm infants with lower gestational ages. Studies have found that as newborns mature neurologically, there is an increase in the proportion of AS, (22,31) which matches the results of the present study, since the preterm infants studied were late preterm.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Therefore, the harmful effects of deprivation, such as impaired development, especially sensorineural, weight gain, length of hospital stay and irritability, among others, should be considered. (31)(32) The preterm infants remained, on average, more time in QS, followed by AS and IS, contrary to a study that reported the predominance of AS, during approximately 80% of the total time, mainly in preterm infants with lower gestational ages. Studies have found that as newborns mature neurologically, there is an increase in the proportion of AS, (22,31) which matches the results of the present study, since the preterm infants studied were late preterm.…”
Section: Discussionmentioning
confidence: 86%
“…(5,10,(29)(30) The preterm infants who were examined slept approximately 57.2% of the 24-hour period, diverg-ing from the literature which indicated that preterm infants, at different gestational ages, had an average of 16 to 18 hours of sleep, corresponding to approximately 70% of 24 hours. (2,31,32) The preterm infants experienced sleep deprivation, even without identification of the influence of handling procedures. Therefore, the harmful effects of deprivation, such as impaired development, especially sensorineural, weight gain, length of hospital stay and irritability, among others, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rats that receive more licking and grooming as pups tend to be less fearful [35], are more likely to explore a novel environment [36], and have an attenuated startle response [37] when tested as adults and compared to rats raised by dams that engage in less licking and grooming. Rats that experience brief (e.g., 15 minutes) periods of maternal separation during the first 2 weeks of life are also less anxious and less stressed as adults [3841]. …”
Section: Introductionmentioning
confidence: 99%
“…This theory, initially proposed by Myron Hofer, has since been substantiated by a multitude of studies across a range of different mammalian species (e.g. (Hofer, 1984; Howell and Sanchez, 2011; Kuhn et al, 1991; Raineki et al, 2014; Rincon-Cortes and Sullivan, 2014). Extending from this foundational theory, variations in caregiving quality and consistency, particularly extreme deviations from the unique species typical pattern of caregiving early in life, further shape an infant's underlying neurobiological processes, leading to life-long alterations.…”
Section: Introductionmentioning
confidence: 94%